Randomized comparison of oesophageal protection with a temperature control device: results of the IMPACT study. Issue 2 (17th November 2020) - Leung, Lisa W M; Bajpai, Abhay; Zuberi, Zia; Li, Anthony; Norman, Mark; Kaba, Riyaz A; Akhtar, Zaki; Evranos, Banu; Gonna, Hanney; Harding, Idris; Sohal, Manav; Al-Subaie, Nawaf; et al.
Abstract: Aims : Thermal injury to the oesophagus is an important cause of life-threatening complication after ablation for atrial fibrillation (AF). Thermal protection of the oesophageal lumen by infusing cold liquid reduces thermal injury to a limited extent. We tested the ability of a more powerful method of oesophageal temperature control to reduce the incidence of thermal injury. Methods and results : A single-centre, prospective, double-blinded randomized trial was used to investigate the ability of the ensoETM device to protect the oesophagus from thermal injury. This device was compared in a 1:1 randomization with a control group of standard practice utilizing a single-point temperature probe. In the protected group, the device maintained the luminal temperature at 4°C during radiofrequency (RF) ablation for AF under general anaesthesia. Endoscopic examination was performed at 7 days post-ablation and oesophageal injury was scored. The patient and the endoscopist were blinded to the randomization. We recruited 188 patients, of whom 120 underwent endoscopy. Thermal injury to the mucosa was significantly more common in the control group than in those receiving oesophageal protection (12/60 vs. 2/60; P = 0.008), with a trend toward reduction in gastroparesis (6/60 vs. 2/60, P = 0.27). There was no difference between groups in the duration of RF or in the force applied ( P value range= 0.2–0.9). Procedure duration and fluoroscopy duration were similar ( P = 0.97, P = 0.91, respectively). Conclusion : Thermal protection of the oesophagus significantly reduces ablation-related thermal injury compared with standard care. This method of oesophageal protection is safe and does not compromise the efficacy or efficiency of the ablation procedure.